(untitled) (International Journal of Scientific Pediatrics, 2023)
In the study of the etio-pathogenesis of endometriosis, the study of the molecular-biological specificity of eutopic and ectopic endometrium - the expression of estrogen and progesterone receptors, proliferation, apoptosis, adhesion, angiogenesis, and cell invasion markers is one of the promising directions. The purpose of the work: to study the molecular-biological characteristics of adenomyosis and ovarian endometriosis in the proliferative phase of the menstrual cycle in women of reproductive age without other gynecological pathologies. Materials and methods: In this study, biopsies of premenopausal (18-51 years 60 biopsies) and postmenopausal women (age 51 and older, 20 biopsies) who underwent hysterectomy between 2019 and 2022 were examined by immunohistochemical methods. In this study, in 2019-22 AVPAB examined 80 adenomyosis and ovarian endometriosis biopsies, immunohistochemical examination of estrogen and progesterone hormonal activity disorders showed that in 60-90% of cases, progesterone, and in 50-70% of cases, estrogen hormone leads to the development of uterine adenomyosis and glandular hyperplasia of the uterus. atypical development of the endometrium and transition to a malignant tumor disease was observed. Ki-67 and p53 were shown in 20% of postmenopausal patients with the transition to the initial state of a low-grade tumor of the uterus.